Pronóstico de la producción de petróleo crudo en el Perú, 2022-2023 - Flores Juárez, José Aldair (2024)
The objective of this research is to determine the best model for the monthly forecast of oil production for 2022 and 2023, for which the Box-Jenkins methodology was used, making use of BCRP data for the estimation of time series models. In the results it was observed that in 2020 crude oil production was affected by COVID - 19; in addition, stationary and trend components were found, and that the resulting model would be a Holt Winter given the repetitive pattern in the stationary component. Finally, it is concluded that the best model found for monthly crude oil production in Peru would be a Holt Winter, obtaining predicted values for the next 12 months, values located in intervals of 80% and 95% that follow the dynamics of the monthly crude oil production.